Forecasting Foreign Exchange Rates Using Recurrent Neural Networks : The Role of Political Uncertainty - Pyörälä, Sanna (My University, 2021)
In June 2016, the majority of UK citizens voted to leave the EU (Brexit). The referendum outcome took both citizens and policymakers by surprise. No other member state has ever left the EU. As a result, the global stock and currency markets collapsed. The impact of uncertainty on financial markets has been studied for decades (Garfinkel, 1999). Studies show that political instability has a significant impact on economic performance. In addition to the market fluctuation, it has been found to increase the unemployment rate and decrease consumers’ and companies’ willingness to invest. Thus, prolonged political instability may lead to a scenario in which the capital moves less, the quality of public services decreases, and economic growth slows down. (Carmignani, 2003; Canes-Wrone et al., 2014). Exchange rate forecasting is an important area of financial research that has recently received more popularity due to its dynamic nonlinear features. In the past, exchange rates have been analyzed using traditional financial models. However, recently academics have started to use artificial learning approaches alongside the traditional ones. In particular, neural networks have been used in time series modeling, and thus exchange rates have been modeled with neural networks. Machine learning aims to improve efficiency and make financial forecasting more automated. The empirical part of this analysis is carried out using a recurrent neural network architecture known as the Long Short Term Memory (LSTM). The LSTM model enables the analysis of non-linear data as well as the detection of diverse cause-and-effect relations. Therefore, it is reasonable to believe that accurate results can be obtained using this approach. The results are analyzed by comparing two different error values - the Mean Squared Error and the Absolute Mean Error. The results prove that the LSTM model is capable of modeling exchange rate values even in times of high volatility. As the Brexit-related uncertainty is higher, the predictability of the Pound to Euro and Dollar decreases. This finding is consistent with previous studies that have shown that political instability reduces the predictability of exchange rates. On the contrary, as the uncertainty surrounding Brexit increased, the predictability of the Pound to Yen improved. This result can partly be explained by the Safe Haven effect, according to which the value of the Yen rises as the values of other developed countries’ currencies fall. Finally, it can be stated that exchange rates are complex financial instruments whose volatility is influenced by a variety of factors and this study is able to produce new perspectives for further research.

Kesäkuussa 2016 enemmistö Iso-Britannian kansasta äänesti EU:sta eroamisen puolesta (Brexit). Kansanäänestyksen tulos yllätti niin kansalaiset kuin vallanpitäjätkin. Mikään muu jäsenvaltio ei ole aikaisemmin eronnut EU:sta. Tämän seurauksena valuutta- sekä osake-markkinat romahtivat globaalisti. Epävarmuuden vaikutusta rahoitusmarkkinoihin on tutkittu jo vuosikausien ajan (Garfinkel, 1999). Tutkimukset todistavat, että poliittisella epävakaudella on merkittävä vaikutus taloudelliseen suorituskykyyn. Rahoitusmarkkinoiden heilunnan lisäksi sen on todettu lisäävän työttömyyttä sekä vähentävän kuluttajien ja yritysten investointihalukkuutta. Täten pitkittynyt poliittinen epävakaus voi johtaa tilanteeseen, jossa pääoma liikkuu hitaammin, julkisten palvelujen laatu heikentyy sekä talouskasvu hidastuu. (Carmignani, 2003; Canes-Wrone ym., 2014). Valuuttakurssien ennustaminen on tärkeä rahoituksen tutkimusala, joka on kasvattanut suosiotaan sen haastavien ja epälineaaristen piirteiden vuoksi. Aikaisemmin valuuttakursseja on tutkittu perinteisillä rahoituksen menetelmillä, mutta lähivuosina tutkijat ovat alkaneet hyödyntämään yhä enemmän koneoppimista perinteisten mallien rinnalla. Erityisesti neuroverkkoja on hyödynnetty aikasarjojen mallintamisessa ja täten myös valuuttakursseja on mallinnettu neuroverkoilla. Koneoppimisen malleilla pyritään tekemään rahoitusmarkkinoiden ennustamisesta tehokkaampaa ja itseohjautuvampaa. Tämä tutkimus hyödyntää empiirisessä osuudessa takaisinkytketyn neuroverkon arkkitehtuuria nimeltä pitkäkestoinen lyhytkestomuisti (Long Short Term Memory, LSTM). LSTM-arkkitehtuuri mahdollistaa epälineaarisen datan analysoinnin sekä monipuolisten syy-seurausketjujen hahmottamisen. Näin ollen on perusteellista uskoa, että tällä metodilla on mahdollista saavuttaa tarkkoja tuloksia valuuttakursseja analysoitaessa. Tulosten analysointi toteutetaan vertailemalla eri valuutoilla saatavia virhearvoja (keskihajonta sekä absoluuttinen keskivirhe). Tulokset todistavat, että LSTM-malli on kykenevä mallintamaan valuuttakurssien arvoja myös epävakaina aikoina. Euron ja dollarin ennustettavuus heikentyy tutkituilla ajanjaksoilla, kun Brexitiin liittyvä epävarmuus lisääntyy. Tämä tutkimustulos on johdonmukainen aikaisemman tutkimuksen kanssa, jonka perusteella on todettu, että valuuttakurssien ennustettavuus heikentyy poliittisen epävarmuuden seurauksena. Jenin ennustettavuus taas päinvastoin paranee ajanjaksolla, kun Brexitiin liittyvä epävarmuus lisääntyy. Tämä tulos voidaan osittain perustella turvasatamailmiöllä, jonka mukaan jenin arvo nousee, kun muiden kurssien arvot laskevat. Lopuksi todetaan, että valuuttakurssit ovat monimutkaisia rahoitusinstrumentteja, joiden heilahteluun vaikuttaa useita eri tekijöitä. Tästä huolimatta, tämä työ onnistuu tarjoamaan uusia näkökulmia tulevaisuuden tutkimukselle.
Keywords: brexit; valuuttakurssit; neuroverkot; koneoppiminen; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance